PUBLICATIONS OF THE WEEK. (Bookseller, 2004)
This article presents information on the section "Publications of the Week" of the April 23, 2004 issue of the periodical "The Bookseller." "Publications of the Week" is a service consisting of newly-published titles. The list in the article is prepared by the company Nielsen BookData and contains titles published in 2004 filed by classification and alphabetically under author. More comprehensive bibliographic information including over five million titles along with enriched information, and publisher and distributor details are available through a range of services provided by Nielsen BookData.